Presença de uma ausência: leitura de uma foto jornalística (Significação: Journal of Audiovisual Culture, 2003)
Because of the concurrence of the TV and the Internet, Journal has been suffering a re-stmcturing, in order to find out its specific place in the media set. These changes are particularly visible in the new functions attributed to the photography - which go beyond the traditional "illustrations" and "reference documentation". Considering such conception, this work proposes, from a specific photo, published in Folha de S. Paulo, to raise questions about the new photography statute in printjournalism, which has started to change around sixties and suffered particular increment with the new informational technology advent. Therefore, this work convokes not only the classical Roland Barthes text, A Cdmara Clara, but also notions of "semi-symbolic", by Jean-Marie Floch and of "presence" by Ric Landowski.